2017
DOI: 10.1071/wf16152
|View full text |Cite
|
Sign up to set email alerts
|

Spatial scales influence long-term response of herbivores to prescribed burning in a savanna ecosystem

Abstract: Both wild and prescribed fire in savanna ecosystems influence habitat use by herbivores by creating or maintaining spatial and temporal heterogeneity in forage quality and vegetation cover. Yet little is known about how spatial scales influence long-term persistence of fire effects. We examined changes over a 6-year period in herbivore preference for experimentally burned patches that varied in spatial extent and grain. Avoidance for the burns by elephants and preference for the burns by impala and Grant’s gaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Additionally, continued frequent fires may decrease soil nutrients and plant forage quality over time (Anderson et al, 2007; Blair, 1997). Nonetheless, Kimuyu et al (2017) found herbivore preferences for burnt areas can still be seen many years after a fire, potentially explaining the increased preference for open‐structured, frequently burnt plots shown by the pure grazers sable antelope, waterbuck, buffalo and plains zebra in this study, as found elsewhere (Burkepile et al, 2013, 2016; Kingdon et al, 2013; Mandinyenya et al, 2020; Traill, 2004; Wirtz & Kaiser, 1988). Similarly, the mixed‐feeding impala showed a strong preference for frequently burnt plots in this study (Ford et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, continued frequent fires may decrease soil nutrients and plant forage quality over time (Anderson et al, 2007; Blair, 1997). Nonetheless, Kimuyu et al (2017) found herbivore preferences for burnt areas can still be seen many years after a fire, potentially explaining the increased preference for open‐structured, frequently burnt plots shown by the pure grazers sable antelope, waterbuck, buffalo and plains zebra in this study, as found elsewhere (Burkepile et al, 2013, 2016; Kingdon et al, 2013; Mandinyenya et al, 2020; Traill, 2004; Wirtz & Kaiser, 1988). Similarly, the mixed‐feeding impala showed a strong preference for frequently burnt plots in this study (Ford et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although the broad trends in mammal responses to resource gradients (Hopcraft et al, 2010) and the immediate response of mammal species to fire have been well‐studied (Eby et al, 2014; Green et al, 2015; Sensenig et al, 2010; Zavala & Holdo, 2005), different species may also respond differently to the longer‐term effects of fire (Bell, 1971; Kimuyu et al, 2017). Understanding mammal responses to differences in long‐term mean fire frequency is thus necessary for the management and conservation of species and habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling of fire–herbivory interactions in a different grassland ecosystem suggested that herbivory reduced fire behavior more than previous fire alone, but these differences declined with time, and disappeared for some fire metrics within 3–4 years (Starns et al, 2019). In a separate set of burn experiments in this ecosystem (Sensenig et al, 2010), both 1‐ha continuous and patchy (30 × 30 m) burns were no longer attractive to herbivores 6–7 years after fire (Kimuyu et al, 2017). Intermediate‐size burns 9‐ and 81‐ha patchy were the most attractive, while large‐size 81‐ha continuous burns were less attractive.…”
Section: Discussionmentioning
confidence: 99%
“…The interactions between fire and herbivory on fuel loads and fire impacts are likely dependent on the spatial scales of these processes (Collins and Smith 2006, Kimuyu et al 2017). Most studies have examined fire–herbivory impacts on fuel loads at intermediate to landscape‐level scales (Waldram et al 2008, Hempson et al 2019).…”
Section: Introductionmentioning
confidence: 99%